What goes around, comes around? Access and allocation problems in Global North–South waste trade - Benedetta Cotta (International Environmental Agreements: Politics, Law and Economics, 2020)
Infamous cases of toxic waste trade and research on its health and environmental implications have made the global waste trade a prominent environmental and social justice issue. Recently, such trade has shifted towards extracting resources from waste as recyclable components and used goods which could create income-generating opportunities and reduce the environmental burdens of waste trade from Global North to Global South countries. Nevertheless, studies highlight persistent problems in the access to these resources and allocation of responsibilities, risks and burdens from processing and disposal of traded waste in Global South countries. This article aims to contribute to the lessons learnt on access and allocation with respect to waste trade by focusing on issues of equity, fairness and distributive justice. Two cases are analysed: trade in discarded electronic and electric equipment (EEE) between the EU and Africa and trade in plastic materials between the UK and China. This study shows that exports of used EEE and recyclable plastic materials exacerbate the environmental burdens of Global South countries while also exporting new environmental risks and social burdens. At the same time, new demands for justice have emerged from Global South countries through waste ship back initiatives, and new international measures have also been adopted. While the access and allocation lens enabled the identification of persistent problems in Global North–South waste trade, directing future Earth System Governance research to the demands emerging from the Global South countries could offer insights into how to better address these problems and deal with growing global inequalities.
Keywords: 330; Access and allocation; Global North–South countries; Global waste trade; Discarded EEE; Recyclable plastic material